In service of the truth?: an evaluation of the Danish Independent Police Complaints Authority - Holmberg, Lars (European journal of criminology, 2019)
The article discusses police oversight systems. In the Nordic countries, the primary focus of external oversight is on individual accountability, and the article reports on results from an evaluation of the Danish Independent Police Complaints Authority (IPCA), established in 2011. Results show that the vast majority of complaints are not upheld, and that most complainants are dissatisfied with their experience with the system. They find the case processing time too long, they think the Authority is prejudiced in favour of the police, and they do not understand the reasoning behind the decisions. The article argues that disappointment is related to the fact that the IPCA focuses almost exclusively on individual wrongdoing (rarely finding sufficient evidence to take action), whereas complainants seek recognition and wish to hold the police organization accountable. It is suggested that the complaints system should be redirected towards mediation between officers and citizens and include a focus on organizational accountability.